Effect of Compaction Energy on Engineering Properties of Expansive Soil - Sadam Hussain (Salehan Institute of Higher Education, 2017)
Swelling of expansive clays is one of the great hazards, a foundation engineer encounters. Each year expansive soils cause severe damage to residences, buildings, highways, pipelines, and other civil engineering structures. Strength and deformation parameters of soils are normally related to soil type and moisture. However, surprisingly limited focus has been directed to the compaction energy applied to the soil. Study presented herein is proposed to examine the effect of varying compaction energy of the engineering properties i.e. compaction characteristics, unconfined compressive strength, California bearing ratio and swell percentage of soil. When compaction energy increased from 237 KJ/m3 to 1197 KJ/m3, MDD increased from 1.61 g/cm3 to 1.75 g/cm3, OMC reduced from 31.55 percent to 21.63 percent, UCS increased from 110.8 to 230.6 KPa, and CBR increased from mere 1 percent to 10.2 percent. Results indicate substantial improvement in these properties. So, compacting soil at higher compaction energy levels can provide an effective approach for stabilization of expansive soils up to a particular limit. But if the soil is compacted more than this limit, an increase in swell potential of soil is noticed due to the reduction in permeability of soil.